Psychological Autopsy: A Method to Assist in the Identification of Risk and Protective Factors for Intimate Partner Femicide - McPhedran, Samara (Violence against women, 2022)
The most common form of violence experienced by women is that perpetrated by intimate partners, and the gendered nature of intimate partner femicide (IPF) has received particular attention. Few studies to date have delved into the limitations associated with methods used in IPF research, and particularly the methods used to study homicide victims (rather than homicide perpetrators). This article outlines dominant methodologies used to study IPF, and considers a novel method of investigation—the “psychological autopsy”—that may help to improve existing knowledge about IPF.